Empirical evidence on the global minimum tax: what is a critical mass and how large is the substance‐based income exclusion? - Devereux, MP; Paraknewitz, J; Simmler, M (Wiley, 2023)
This paper presents empirical evidence on the proposed global minimum tax (GMT) of the OECD's Pillar 2. First, it addresses how many, and which, countries or country groups can be seen as constituting a ‘critical mass’ for its successful implementation; given such a critical mass, remaining jurisdictions worldwide will have an incentive to implement the GMT as well. Second, it assesses the generosity of the substance-based income exclusion (SBIE), which is informative for the revenue collected under the GMT.